Decellularized Extracellular Matrix for Bioengineering Physiomimetic 3D in Vitro Tumor Models. Issue 12 (December 2020) - Ferreira, Luís P.; Gaspar, Vítor M.; Mano, João F.
Abstract : Recent advances in the extraction and purification of decellularized extracellular matrix (dECM) obtained from healthy or malignant tissues open new avenues for engineering physiomimetic 3D in vitro tumor models, which closely recapitulate key biomolecular hallmarks and the dynamic cancer cell–ECM interactions in the tumor microenvironment. We review current and upcoming methodologies for chemical modification of dECM-based biomaterials and advanced bioprocessing into organotypic 3D solid tumor models. A comprehensive review of disruptive advances and shortcomings of exploring dECM-based biomaterials for recapitulating the native tumor-supporting matrix is also provided. We hope to drive the discussion on how 3D dECM testing platforms can be leveraged for generating microphysiological tumor surrogates that generate more robust and predictive data on therapeutic bioperformance. Highlights: Despite the remarkable potential of scaffold-based 3D multicellular tumor models as preclinical screening platforms, currently used ECM-mimetic biomaterials fail to fully mimic the biomechanical and biomolecular complexity of the tumor ECM. Decellularized extracellular matrix (dECM) 3D tumor models recapitulate key ECM components and cancer stromal cell–ECM interactions, providing significant advantages over currently available in vitro testing platforms. State-of-the-art decellularization and processing methodologies contribute with key advances toward preserving key ECM components and incorporating dECM into complex multicellular 3D microtumor assembly strategies. Integrating dECM 3D in vitro tumor models into high-throughput screening platforms and analysis via multiomics and single-cell profiling will unlock new avenues for developing more predictive and physiomimetic 3D tumor models.